2010
DOI: 10.1080/01426390903407152
|View full text |Cite
|
Sign up to set email alerts
|

‘… Silver in the Stars and Gold in the Morning Sun’: Non-farm Rural Landowners' Motivations for Rural Living and Attachment to their Land

Abstract: Studies have identified that, given the opportunity, the majority of North Americans would prefer to live in small towns and rural areas. This preference is based in aesthetic notions linked to landscape features, personal meaning, and perceptions. In order to understand how the growing non-farm rural landowner population will influence the rural landscape, this research explored the motivations of non-farm rural landowners for living in rural areas, and their perceptions of their property. It involved five pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Economic research has focused on the monetary valuation of amenities through surveysusing the willingness to pay method (Bergstrom and Ready 2009). A lot of research contributes to understanding the impact of amenities for local development (Matsuoka and Kaplan 2008, Banzhaf 2010, Milburn et al 2010. However, many studies related to the willingness to pay for amenities show that it is not affiliated with the needs of policy makers in land planning (Banzhaf 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Economic research has focused on the monetary valuation of amenities through surveysusing the willingness to pay method (Bergstrom and Ready 2009). A lot of research contributes to understanding the impact of amenities for local development (Matsuoka and Kaplan 2008, Banzhaf 2010, Milburn et al 2010. However, many studies related to the willingness to pay for amenities show that it is not affiliated with the needs of policy makers in land planning (Banzhaf 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The aesthetic value of nature is usually typified by impressive landscapes, such as mountains, forests, and oceans, and interactions with those landscapes have positive effects on human health, including reduced levels of stress and depression (Keniger, Gaston, Irvine, & Fuller, ). Agricultural landscapes may also meet human needs for an appealing aesthetic (Milburn, Brown, & Mulley, ), as evidenced by the persistence of an idealized pastoral scene (Schaman, ). The health benefits of human interaction with nature also extend beyond natural areas, including rural agriculture settings, urban agriculture, and even greenhouses (Keniger et al., ; Uhlmann, Lin, & Ross, ), which is critical due to the high physical and mental health risks associated with farmers (Furey, O'Hora, McNamara, Kinsella, & Noone, ).…”
Section: How Do These Changes Affect Provision Of Ecosystem Services?mentioning
confidence: 99%
“…The expansion of agriculture may leave aesthetic values intact to a certain extent, as humans often show a preference toward symmetry of managed fields (Milburn et al., ), although Klein et al. () reported that appeal of cropland increased with more diverse management (e.g., buffer strips).…”
Section: How Do These Changes Affect Provision Of Ecosystem Services?mentioning
confidence: 99%
See 1 more Smart Citation
“…Urban development also commonly results in increased traffic congestion, which can reduce personal time and impact psychological health (Brueckner, 2000;Frumkin, 2002). Urban growth is also associated with degraded landscape aesthetics, which may be particularly salient for forest owners (Erickson, Ryan, & De Young, 2002) and rural residents (Milburn, Brown, & Mulley, 2010) who tend to value and maintain their forest land for aesthetic instead of monetary reasons. The diverse array of evidence suggesting urbanization has negative ecological and social/psychological impacts provides further support that distance to urban development will negatively influence the likelihood of an individual indicating an intent to sell his/her forest land.…”
Section: Negative Consequences Associated With Urban Developmentmentioning
confidence: 99%